Surrender : How the Clinton Administration Completed the Reagan Revolution - Meeropol, Michael (Book collections on Project MUSE., 2000)
Meeropol gives a detailed account of the inability of the U.S. economy between 1990 and 1994 to improve productivity or raise incomes for most of the population. He contends that the next recession, certain to begin before the end of 1999, will reveal public policymakers' predictions of balanced budgets and millennial prosperity to be hubris of the highest order.